Second opinion and discrepancy in the diagnosis of soft tissue lesions at surgical pathology - Sharif Muhammad; Hamdani Syed Naeem (Wolters Kluwer Medknow Publications, 2010)
Objective: To determine the frequency and magnitude of discrepancies in the surgical pathological diagnosis of soft tissue lesions on review and second opinion in a histopathology center. Study Design: Cross-sectional, observational. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from April 2006 to May 2007. Materials and Methods: All the cases of soft tissue as well as bone lesions, irrespective of age and gender, which were referred for second opinion or review after being reported elsewhere, were included in the study. A panel of antibodies of soft tissue, epithelial and lymphoid markers was applied according to the requirements of each case. The cases were categorized as category A where there was concurrence between initial diagnosis and diagnosis at review. Category B included cases where there was disagreement in the specific diagnostic entity as per WHO classifications without therapeutic implications. Category C was cases where the category of benign or malignant diagnosis remained the same but there was disagreement in the specific diagnosis with definite therapeutic implications. Category D had diagnosis of benign changed to malignant while category E had cases where diagnosis of malignancy was changed to a benign lesion. Results: During the study period, 34 cases of soft tissue lesions were received for review and second opinion. The mean age of the patients was 39 ΁ 22 years and immunohistochemistry was performed in 21 (62%) of 34 cases. Concurrence between the review and initial diagnosis was seen in 18 (53%) cases (category A). Discrepancy in the diagnosis at review and initial consultation was seen in 16 (47%) cases. There were four (11.8%) cases that were placed in category B as the diagnosis of benign and malignant remained the same but the specific diagnostic entity was changed. Category C included eight (23.5%) cases where the review diagnosis changed the therapeutic modality despite the benign or malignant category remaining unchanged. All the cases in this category required immunohistochemistry as diagnosis of metastatic carcinoma was changed to sarcoma in two cases and diagnosis of sarcoma was changed to carcinoma in three cases. There was only one (2.9%) case in category D where a benign diagnosis was changed to malignant on review and three (8.8%) cases reported as malignant had a revised diagnosis of benign lesion, placing them in category E. Conclusion: In the absence of a quality assurance regulatory body to monitor and overlook the professional competence of practicing surgical pathologists, a mandatory review and second opinion should be undertaken whenever a major therapeutic endeavor is to be undertaken, regardless of the cost for the ultimate benefit of the patient.